PEMBARUAN PENDIDIKAN ISLAM MENURUT MUHAMMAD ABDUH - Muqoyyidin, Andik Wahyun (Jurnal Pendidikan Islam, 2016)
This paper is to explore Muhammad Abduh’s thought regarding Islamic education form. The approach used is discourse and figure analysis. The result of the studies towards a number of textbooks shows that education reform by Muhammad Abduh was initialized by formulating foundation the epistemology of Muslim beliefs throught Tajdid al-Fahm (Renewal Islamic Understanding). It meanas that the basic values and principles of variety in Islam are only about the essence that need to be maintained. While the aspect of institutional historicity should be maintained actual fit with the present time, context, and world dynamic. In the context of education, Abduh implemented the priciples above by omitting dualism in education. The principle is that public school should provide religion leason and religion achool asould develope the knowledge. In organizing the materials, the fulfillments to brain and should needs should be kept balanced.